Common Neighbourhood Domination in Some Operations on Fuzzy Graphs - AL-Mekhlafi, Abdullah Q.; Shubatah, Mahiuob M. Q. (IJRDO -JOURNAL OF MATHEMATICS, 2021)
In this paper, the concept of common neighbourhood CN - dominating in some operations on fuzzy graphs and denoted by γcn introduced and investigated the bound of of some operations on fuzzy graphs are obtained such as union, join, Cartesian product and composition.